FAKTOR PEMICU DAN PENENTU KELAYAKAN PEMEKARAN WILAYAH DI SUMATERA BARAT (Pendekatan Sosial dan Ekonomi) - Joan Marta (Ecosains: Jurnal Ilmiah Ekonomi dan Pembangunan, 2012)
This study aims to analyze the socio-economic conditions as a trigger factor and determining the feasibility of splitting of district and municipalities in West Sumatra. This study uses weighting and scores for each of the socio-economic variables. Based on the analysis, there is potential for expansion in the 7 (seven) district in West Sumatra, this occurs most likely driven by the extent of the area owned, so that public services received by the public to be less than the maximum. Besides the area factor here too there are ethnic differences in factors (culture) which can promote regional expansion. Of the seven districts that have the possibility of splitting the area when viewed in terms of feasibility level, the Pesisir Selatan District and District Sijunjung have a very viable category in terms of ability and local financial and human resources quality, while four other districts get qualify for the split.